The age and colors of massive white dwarf stars - Althaus, Leandro Gabriel (2007)
We present evolutionary  calculations and colors for massive white dwarfs with oxygen--neon  cores for masses between 1.06 and  1.28Msolar.  The evolutionary stages computed cover the luminosity range  from log(L/Lsolar)= 0.5 down to -5.2. Our cooling sequences are based on evolutionary calculations that take  into account the chemical composition expected  from  massive white  dwarf  progenitors that  burned carbon  in  partially  degenerate  conditions.  The use of  detailed non-gray model  atmospheres provides us with accurate outer  boundary conditions  for  our evolving  models at  low effective temperatures. We examine the cooling age, colors  and magnitudes of our  sequences.  We find that massive white dwarfs are characterized by very short ages to such an extent  that they reach the turn--off in their colors and become blue at ages well below 10 Gyr.  Extensive tabulations for massive white  dwarfs,  accessible  from   our  web  site,  are  also presented.